Atmospheric ions and new particle formation events at a tropical location, Pune, India. (12th August 2015) - Kamra, A. K.; Siingh, Devendraa; Gautam, A. S.; Kanawade, V. P.; Tripathi, S. N.; Srivastava, A. K.
Abstract : Characteristics of small, intermediate and large ions and nanometre particles, and the influences of environmental conditions and local topography on the interactions of these ions and particles in the size range of 3.85–47.8 nm diameter are studied during new particle formation (NPF) events observed at Pune, India from 20 March to 23 May 2012. During the NPF events, the formation rate of 5 nm particles ranged from 3.5 to 13.9 cm −3 s −1 and growth rates of both positive and negative ions were greater than those of neutral particles. Total ion concentrations in this size range were approximately double on event days than on non‐event days. The NPF events were generally preceded by 2–3 h periods of enhanced concentration of ions and aerosols (PECIA) which are associated with katabatic winds from the surrounding hill‐slopes at our site. During PECIA, ions ≤8 nm diameter grew faster and attained mode diameters greater than those of neutral particles. PECIA provided the ions of sub‐8 nm diameter and dramatically reduced the condensation sinks and thus contributed to the development of conditions conducive for NPF. During PECIA, total concentrations of the ions and particles become almost equal and the Boltzmann charge distribution breaks down. During NPF events, mode diameters of the ions and particles first steeply decreased accompanied by a steep increase in condensation sink but later gradually increased at identical rates. Observations of charging ratio of 3–4 nm particles being higher than the charge equilibrium value and non‐observation of charge equilibrium for >5 nm ions and particles indicate occurrence of ion nucleation and/or advection during the PECIA.